2011
DOI: 10.1021/pr2008994
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Functional Proteomics Strategy for Protein Kinase Inhibitor Validation and Identification ofbona fideProtein Kinase Substrates: Application to Identification of EEF1D as a Substrate for CK2

Abstract: Protein kinases have emerged as attractive targets for treatment of several diseases prompting large-scale phosphoproteomics studies to elucidate their cellular actions and the design of novel inhibitory compounds. Current limitations include extensive reliance on consensus predictions to derive kinase–substrate relationships from phosphoproteomics data and incomplete experimental validation of inhibitors. To overcome these limitations in the case of protein kinase CK2, we employed functional proteomics and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 85 publications
1
28
1
1
Order By: Relevance
“…Gyenis et al 56 developed a strategy combining metabolic labeling with 32 P-orthophosphate with transfection of inhibitor-resistant CK2 mutants to identify and validate inhibitor-responsive proteins as true physiological substrates. Interestingly, the translation factor EF-1-delta was shown to become hypo-phosphorylated on S162 in response to the CK2 inhibitor TBBz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gyenis et al 56 developed a strategy combining metabolic labeling with 32 P-orthophosphate with transfection of inhibitor-resistant CK2 mutants to identify and validate inhibitor-responsive proteins as true physiological substrates. Interestingly, the translation factor EF-1-delta was shown to become hypo-phosphorylated on S162 in response to the CK2 inhibitor TBBz.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies independently identified the orthologous serine residue (S106) in EF1-β as responsive to CX-4945, in good agreement with these data. While the approach developed by Gyenis et al 56 can readily detect inhibitor-responsive kinase substrates in cultured cells, it would be difficult to apply to pre-clinical animal models and is not amenable to analysis of patient samples.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic Analysis and Validation-Four 10-cm plates of scrambled control or shRNA knockdown (sh21) cells were lysed in lysis buffer (8 M urea, 2% CHAPS, 1 mM benzamidine, 25 g/ml leupeptin, 20 g/ml pepstatin A, 20 g/ml aprotinin, 1 M okadaic acid, 1 M microcystin, 1 mM sodium orthovanadate, 0.5% ampholyte, and 40 mM DTT) on ice according to previously established methods (26). The cell lysates were cleared by centrifugation and the protein concentration was measured with a Bradford Protein Assay (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were processed using the MASSPrep Automated Digestor (Waters/Micromass) in the Functional Proteomics Facility at the University of Western Ontario. Peptides were spotted on MALDI plates and MALDI-TOF analysis was performed using a 4700 Proteomics Analyzer (Applied Biosystems, Foster City, CA) as described (26). Mass spectra were searched against the NCBInr data base of Mus musculus using the MASCOT search engine with carbamidomethyl (C) fixed and oxidation (M) plus phosphorylation (ST) variable modification.…”
Section: Methodsmentioning
confidence: 99%
“…Some posttranslational modifications are observed, such as phosphorylation, acetylation and succinylation (https://www.ncbi.nlm.nih.gov). eEF1D can be hyperphosphorylated and the phosphorylations are made by some protein kinases, including casein kinase 2 (Gyenis et al, 2011;Browne and Proud, 2002) and cyclin-dependent kinase 1 ( CDK1) (Kawaguchi et al, 2003). In particular, CDK1 phosphorylates EEF1D at Ser-133 (Kawaguchi et al, 2003).…”
Section: Descriptionmentioning
confidence: 99%